Different forms of the Kadanoff-Baym equations in quantum statistical mechanics: Теория электронных свойств - Kondratyev, A.S.; Shahid, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
A new form of the Kadanoff–Baym equations for a system of interacting particles is offered on the basis of the retarded and advanced quantum Green’s functions. The comparison of the traditional and the offered formsof the equations allows to analyze the question to what extent Landau–Silin kinetic equations for the neutral Fermi-liquid and for the electron liquid of normal metals take into account quickly varying in space and time disturbances.